INTEGRATED MARKETING COMMUNICATION (IMC) CATERING OEMAH ANGLO IN IMPROVING THE IMAGE IN THE EYES OF CUSTOMERS - gilang, jawara (Journal of Language Teaching Lingustics and Literature, 2024)
The use of social networks as a marketing medium is well known and accepted by the public. One of the social media that is often used is Instagram and WhatsApp. One of the advantages of Instagram as a marketing medium is that it can use text and images directly. Instagram also provides the feature of creating a special page or place to market something. Integrated Marketing Communication (IMC) of Oemah Anglo's catering in improving its image in the eyes of customers is interesting to research because so far the creation of Oemah Anglo's advertisements has been carried out self-taught, not using the services of content creators or marketing professionals, thus raising the question of whether Oemah Anglo's marketing communication strategy so far has been able to improve CUstomer trust?. This research uses a qualitative approach method, with 8 informants, namely 1 owner of Oemah Anglo, and 7 customers. The research results concluded that Oemah Anglo catering's integrated marketing communication strategy was appropriate, because in general it was able to increase customer trust. This is proven from the results of interviews with sources who stated that they were satisfied with the products and services from Oemah Anglo, so they ordered again.